Modelling ultrasonic sensor for gas bubble proﬁles characterization of chemical column - Rahiman, M.H.F.; Rahim, R.A.; Rahim, H.A.; Ayob, N.M.N.; Mohamad, E.J.; Zakaria, Z. (Elsevier Science Ltd, 2013)
In this paper, we present a modelling and experimental work to characterize gas bubble proﬁles in chemical column using a pair of ultrasonic sensor. The gas bubble proﬁles from 2.90 mm to 7.50 mm diameter are of interest in this study. The modelling concerns ultrasonic investigation via transmission-mode technique. The modelling estimation was compared with the experimental data and the gas bubble proﬁle characterizations from the chemical column were deduced.